Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5937/univtho7-13753
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of factors affecting the high radon concentration in different types of houses

Abstract: This paper presents an analysis of indoor radon measurements carried out in municipality of Zubin Potok, northwestern part of Kosovo and Metohija. Annual measurements in two rooms of each house were performed by solid state nuclear track detectors commercially known as Gammadata. Average indoor ra don concentration in di fferent type of houses varied from 29-326 Bq/ m 3 . A di fferent year of house's constructi on i ncluding vari ous types of buil ding materials were selected for survey. A detail analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The airtightness of PVC windows probably causes radon accumulation; Jiránek and Kačmaříková ( 2014 ) considered that these practices could lead to 3.4 higher radon concentration, while Yang et al ( 2019 ) reported 4–8 times increasing in radon concentration in some dwellings after thermal retrofitting. Also, lower radon concentrations were reported in old building with wooden joinery than in new building with PVC windows (Gulan 2017 ). Vasilyev et al ( 2015 ) showed the significantly lower ventilation rate in the multi-storey buildings with PVC windows, which in turn causes a high indoor radon concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The airtightness of PVC windows probably causes radon accumulation; Jiránek and Kačmaříková ( 2014 ) considered that these practices could lead to 3.4 higher radon concentration, while Yang et al ( 2019 ) reported 4–8 times increasing in radon concentration in some dwellings after thermal retrofitting. Also, lower radon concentrations were reported in old building with wooden joinery than in new building with PVC windows (Gulan 2017 ). Vasilyev et al ( 2015 ) showed the significantly lower ventilation rate in the multi-storey buildings with PVC windows, which in turn causes a high indoor radon concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained negative correlation can be explained by the fact that in addition to the content of the radium in the soil, a large number of factors affect the concentration of indoor radon: soil permeability and moisture, building materials used in the construction, meteorological conditions, ventilation, type of heating, etc. (UNSCEAR, 2008, Gulan, 2017, but probably the most important factor is the content of 226 Ra in deeper layers of the ground. Almost all values of radon concentration in kindergartens and schools in Niš are below the limit of 200 Bq/m 3 .…”
Section: Resultsmentioning
confidence: 99%